2021
DOI: 10.1016/j.psj.2021.101314
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of semen collected from gander included in the genetic resources conservation program

Abstract: Conservative breeding ex situ in vivo is one of the most popular methods of creating genetic reserves. Unfortunately, keeping animals in small closed populations leads to inbreeding which reduces their reproductive capacity. The aim of the study was to characterize the sperm quality of 6 genetic groups of geese (northern and southern breeds) kept in Poland for many generations as genetic reserve flocks. Each breed was represented by 10 randomly selected 1-yr-old ganders, semen was collected 14 times, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(59 reference statements)
4
9
0
Order By: Relevance
“…In the presented experiment, as in studies of other authors, a large breed and individual male variations in quantitative and qualitative semen traits were observed. The obtained average semen volumes (0.18–0.40 ml) are comparable with other regional goose breeds (0.16–0.41 ml, Łukaszewicz et al., 2021), but definitely lower than those of White Roman gander in Chang et al. (2016) study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the presented experiment, as in studies of other authors, a large breed and individual male variations in quantitative and qualitative semen traits were observed. The obtained average semen volumes (0.18–0.40 ml) are comparable with other regional goose breeds (0.16–0.41 ml, Łukaszewicz et al., 2021), but definitely lower than those of White Roman gander in Chang et al. (2016) study.…”
Section: Discussionsupporting
confidence: 78%
“…In this study we observed more positive responses to massage in all breeds compared to the results obtained in our previous studies on Polish regional goose Kartuska and Rypińska (36.4% and 44.3%), while the reactions of foreign breeds were similar to Suwalska, Kielecka, Lubelska and Podkarpacka geese (57%–58.6%) (Łukaszewicz et al., 2021). Nevertheless, in all analysed breeds, the ganders’ susceptibility to massage was much lower than of commercial line White Koluda ® (nearly 83%; Łukaszewicz & Kruszyński, 2003) or Canada goose ( Branta canadensis ; 61%; Zaik, 2013).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The collection method largely influences the quality of the collected semen. The ability to avoid contaminants in the semen and to minimise handling stress to the birds are two fundamental aspects of a collection technique [ 30 , 31 , 32 , 33 , 34 ]. Therefore, semen collection should be considered the first essential factor for the cryopreservation process and successful AIs.…”
Section: Introductionmentioning
confidence: 99%